Influencia del azúcar como componente de una solución de salmuera, en las características físicas y sensoriales del camarón de exportación congelado por aspersión y su efecto en el proceso. - Álava Gutiérrez, Jorge (2010)
Traditionally, shrimp industries use solutions of brine constituted by salt for the process of freezing, nevertheless, long times in the aspersion of brine process of frozen shrimp affect on the physical and sensory characteristics of the product because of the exhibition of the product to the brine causing sensory unacceptability for the acquired salty flavor. In addition, the process time affects at the formation of big crystals in the product that cause injuries in the cellular fabric of the shrimp and consistently the increase of the exudation of fluids intra celular of the product. On the other hand, when these times of process are very short it is not achieved to obtain a satisfactory freezing of the final product. This thesis proposes to evaluate the process conditions of the brine which composition includes sugar as way of freezing and as influential factor in the physical and sensory characteristics of the shrimp (Penaeus Vannamei). For the new brine formulation, it is necessary to establish controls of process parameters such as times and temperatures of processing which will allow to increase the time of useful life of the brine in 50 % in relation at the traditional time, this will allow to optimize the use of the brine and define the process parameters that we find it is possible to obtain a percentage of chlorides in the shrimp of 0,51 % which is perceived by the consumer as agreeably and simultaneously obtain a percentage of exudation of the product of 4 % not to detect problems in the texture of the shrimp, the above mentioned conditions are acquired under process parameters from 300 seconds to-15 ºC.